DISTRIBUSI HARTA PUSAKA DALAM TRADISI PRENGKENIN PADA MASYARAKAT MUSLIM DESA BAGIK PAYUNG TIMUR NUSA TENGGARA BARAT (Ahkam: Jurnal Hukum Islam, 2022)
The distribution of inheritance through the Prengkenin custom is the appointment or attribution of certain assets to heirs by parents that will be owned immediately or after the parents die. The distribution of inheritance through prengkenin produces two patterns, a) grants, the appointment of certain assets that can be owned immediately, and b) wills, assets that will be owned after the parents die. The share of each heir is determined regarding to an agreement of them witnessed by traditional leaders with the aims patuh-patuh, bagus-bagus, solah-solah (getting along with other heirs) and pacu-pacu (maintaining politeness). Those can describes tolerance and mutual respect to others. The share between men and women use the principle of â€œmama memonggok, nina nyenyionâ€ (men shouldering, women carrying). It describes the role of them that will then affect the number of their share. Meanwhile, the reasons for the BPT Village Community to distribute inheritance through prengkenin are, a) avoiding heirs conflicts in the future. b) distributive justice c) dissatisfaction on the traditional fiqh of inheritance system.